1997
DOI: 10.3354/meps157097
|View full text |Cite
|
Sign up to set email alerts
|

Sinking rate versus cell volume relationships illuminate sinking rate control mechanisms in marine diatoms

Abstract: It has been shown that for dead marine diatom cells or diatom cells which are severely stressed metabolically, larger cells sink faster than small cells as dictated by Stokes' Law. In these cases, the slope of the sinking rate versus cell volume relationship within a culture reaches a maximum. Within cultures of rapidly dividing cells, larger cells' s~n k i n g rate is reduced physiologically to that of smaller cells and the slope of this relationship approaches zero. In several marine d~a t o m species betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
115
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(122 citation statements)
references
References 3 publications
5
115
0
Order By: Relevance
“…Stokes' law predicts how quickly a spherical diatom should sink given a certain overall cell density, r tot . As previously described, diatoms reduce their density through ion exchange, a physiologically costly process (Anderson and Sweeney 1978;Waite et al 1992). In the absence of physiological density reduction, diatoms sink at their maximum speed, which should be governed solely by fluid mechanics (Waite et al 1997).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Stokes' law predicts how quickly a spherical diatom should sink given a certain overall cell density, r tot . As previously described, diatoms reduce their density through ion exchange, a physiologically costly process (Anderson and Sweeney 1978;Waite et al 1992). In the absence of physiological density reduction, diatoms sink at their maximum speed, which should be governed solely by fluid mechanics (Waite et al 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Diatoms fit the assumptions of Stokes' law: they are small, roughly spherical, and slow moving. Nonetheless over the last 50 yr, empirical measurements of diatom sinking speeds have shown that the power-law relationship between radius and velocity has a scaling exponent between 1.2 and 1.6 (Smayda 1970;Waite et al 1997). This mismatch between empirical observation and theory has often been noted, (Walsby and Reynolds 1980;Reynolds 2006), but the physical basis for the mismatch is yet to be resolved.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Carbon (pg C cell Bertilsson et al 2003, Heldal et al 2003, and Verity et al 1992 Values taken or calculated from Johnson et al 2009, Durand et al 2002, and Montagnes et al 1994 Values taken or calculated from Waite et al 1997 andMontagnes et al 1994. Table 2 for references.…”
Section: Speciesmentioning
confidence: 99%